Frontal electroencephalogram activity during emergence from general anaesthesia in children with and without emergence delirium. (January 2021) - Kim, Jonghae; Lee, Hyung-Chul; Byun, Sung-Hye; Lim, Hyunyoung; Lee, Minkyu; Choung, Yoojin; Kim, Eugene
Abstract: Background: Emergence delirium (ED) in children after general anaesthesia causes significant distress in patients, their family members, and clinicians; however, electroencephalogram (EEG) markers predicting ED have not been fully investigated. Methods: This prospective, single-centre observational study enrolled children aged 2–10 yr old under sevoflurane anaesthesia. ED was assessed according to Diagnostic and Statistical Manual of Mental Disorders (DSM) IV or 5 criteria. The relative power of low-frequency (delta and theta) and high-frequency (alpha and beta) EEG waves during the emergence period was compared between the children with and without ED. The linear relationships between the relative power and peak Paediatric Assessment of Emergence Delirium (PAED) score were investigated. Results: Among the 60 patients, 22 developed ED (ED group), whereas the other 38 did not (non-ED group). The relative power of the delta wave was higher (mean [standard deviation], 0.579 [0.083] vs 0.453 [0.090], respectively, P <0.001) in the ED group, whereas that of the alpha and beta waves was lower in the ED group, than in the non-ED group (0.155 [0.063] vs 0.218 [0.088], P =0.005 and 0.114 [0.069] vs 0.186 [0.070], P <0.001, respectively). The areas under the receiver operating characteristic curves of the relative power of the delta wave, low-to-high frequency power ratio, and delta-to-alpha ratio were 0.837 (95% confidence interval, 0.737–0.938), 0.835 (0.735–0.934), and 0.768 (0.649–0.887), respectively. The relative power of the delta wave and the two ratios had a positive linear relationship with the peak PAED scores. Conclusions: Paediatric patients developing ED have increased low-frequency (delta) frontal EEG activity with reduced high-frequency (alpha and beta) activity during emergence from general anaesthesia. Clinical trial registration: NCT03797274 .